Urgensi Profesionalisme Guru sebagai Solusi Atas Krisis Moral dan Tantangan Pendidikan Era Global di Indonesia - Muthmainnah Choliq; Nadhilla Claryzha Sifana Dewi; Yulia Amanda Putri Hibatullah; Zila Gustita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Moral crisis and educational challenges in the era of globalization are hot issues currently being faced by the world of education in Indonesia. The purpose of this study is to examine the urgency of teacher professionalism in Indonesia for solutions to the moral crisis and educational challenges in the global era. In the midst of rapid social change, globalization, and the degradation of moral values ​​among students, the teaching profession is expected not only to be limited to teaching, but also to build national character. This study uses a library research method with a descriptive-qualitative approach, through a review of various literature such as books, scientific journals, and previous relevant research. The results of the study indicate that teacher professionalism which includes pedagogical, professional, social, and personality competencies has an important role in creating an adaptive, moral, and quality education system. Strengthening teacher professionalism is the first strategic step in forming a generation with character that is able to face global challenges without losing the nation's identity.